2012
DOI: 10.1093/ejcts/ezs451
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of transcatheter techniques for intracardiac and extracardiac cavocaval connection in principle for Fontan completion in chronic animal models

Abstract: Transcatheter techniques for completion of cavocaval connection in surgically simulated, chronic animal models is safe and feasible. Both techniques were equally successful with no failures or short-term complications. Such techniques should work in principle for completion of intracardiac and extracardiac Fontan circulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Similar to the stepwise procedure in humans, a gradual adaptation of the cardiovascular system to the altered hemodynamic condition may be an option for an animal model. Different attempts to establish parts of the Fontan circulation using a transcatheter approach alone 38,39 or in a combined surgical preconditioning and completing interventional approach [40][41][42][43][44][45][46][47][48] have been reported during the last two decades. Such a procedure would reduce the risk of reoperation (especially bleeding and injuries to lungs and heart) and a second CPB run could be avoided, which is certainly beneficial for cardiac function.…”
Section: Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the stepwise procedure in humans, a gradual adaptation of the cardiovascular system to the altered hemodynamic condition may be an option for an animal model. Different attempts to establish parts of the Fontan circulation using a transcatheter approach alone 38,39 or in a combined surgical preconditioning and completing interventional approach [40][41][42][43][44][45][46][47][48] have been reported during the last two decades. Such a procedure would reduce the risk of reoperation (especially bleeding and injuries to lungs and heart) and a second CPB run could be avoided, which is certainly beneficial for cardiac function.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…49 Still, it has been shown that interventional creation of a superior cavopulmonary connection with the usage of long covered stents, 39 intervascular connections as the interventional Potts shunt, 50 or interventional completion of Fontan are possible in animals and also in humans. 40,[42][43][44][45][46][47][48]51 The different anatomical features in animals and the nowadays limited availability of endovascular catheter materials make the creation of a solely interventional superior cavopulmonary connection difficult. Most likely, such a procedure will result in a connection between the SVC and the right lower lobe PA, directing most of the blood flow to the right lower lobe.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…The ultimate goal of univentricular palliation is completion of the total cavopulmonary connection, where all systemic venous blood is directed into the pulmonary arteries bypassing the heart. Transcatheter total isolation of the caval venous blood flow from the cavity of the right atrium by deployment of a long covered stent between the orifices of both caval veins in pig and sheep is technically feasible [24,25]. However, this approach will be unsuitable after applying the transcatheter technique of the bidirectional Glenn anastomosis proposed in our study.…”
Section: Bidirectional Superior Cavopulmonary Anastomosismentioning
confidence: 83%
“…Other methods for deploying covered stents to connect the IVC with the PA have been described in human and animal studies 1‐5,7 . First, Glenn circulation was established with subtotal banding of the SVC at the cavoatrial junction, and an ePTFE tube sutured around the suprahepatic IVC end to provide a landing zone inferiorly in 10 viable sheep.…”
Section: Discussionmentioning
confidence: 99%
“…Transcatheter Fontan completion is a dream for interventional cardiologists yet to be fully realized despite many attempts in animals and humans and lacks consensus for practice 1‐10 . We describe the development of a novel stent and balloon‐in‐balloon (BIB) system for transcatheter Fontan completion.…”
Section: Introductionmentioning
confidence: 99%